Pengaruh Sektor-Sektor Pariwisata terhadap Pertumbuhan Ekonomi Sumatera Utara - Harahap, Kobul; Sirojulizam, Sirojulizam; Syafii, M. (Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of hotel room occupancy rates, average length of stay of foreign tourists, and average length of stay of domestic tourists on the economic growth of North Sumatra. This study uses secondary data from 2013-2022 in eight regencies surrounding Lake Toba. The analysis model used is a panel data analysis model using the Eviews analysis tool. The results of the study revealed that hotel room occupancy rates, average length of stay of foreign and domestic tourists and the number of accommodations have a simultaneous effect on the economic growth of North Sumatra, but partially the average length of stay of foreign tourists, the average length of stay of domestic tourists and the number of accommodations do not have a significant effect on economic growth.